Can mobile phone-based animated videos induce learning and technology adoption among low-literate farmers? A field experiment in Burkina Faso - Maredia, Mywish K.; Reyes, Byron A.; Ba, Malick N.; Dabiré, Clementine L.; Pittendrigh, Barry Robert; Bello-Bravo, Julia (Informa UK Limited, 2018)
This article explores an innovative approach to deliver information about new agricultural technology that combines a versatile and potentially lower cost method of developing animated videos with another low-cost method of sharing it on mobile devices (i.e. mobile phone). It describes a randomized controlled field experiment conducted in Burkina Faso to evaluate the effectiveness of animated videos shown on mobile phone compared with the traditional extension method (live demonstration) in inducing learning and adoption of two post-harvest technologies among low-literate farmers. Results suggest that video-based training was as effective as the traditional method in inducing learning and understanding. For technologies that farmers were already aware of animated video shown on the mobile phone was also as effective as live demonstration in inducing adoption. However, in transferring new technologies, the traditional method was more effective in inducing adoption at p < .10, but not at p < .05. Potential role of mobile phone-based videos as part of the agricultural extension system is discussed.